2008
DOI: 10.1044/1092-4388(2008/075)
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Mechanisms of Speech Perception in Noise

Abstract: We found cortical task-independent and noise-dependent effects concerning speech perception in noise involving bilateral mSTG and left pSTG. These results likely reflect demands in acoustic analysis, auditory-motor integration, and phonological memory, as well as auditory attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
116
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 66 publications
13
116
2
1
Order By: Relevance
“…In contrast to the current findings, Wong, Uppunda, Parrish, and Dhar (2008) observed that the STG was more active during listening to speech in noise relative to listening to speech in quiet. However, in line with the relation between RSpan and the STG activation as observed in the current study, they suggested a role of the STG in a phonological working memory network.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to the current findings, Wong, Uppunda, Parrish, and Dhar (2008) observed that the STG was more active during listening to speech in noise relative to listening to speech in quiet. However, in line with the relation between RSpan and the STG activation as observed in the current study, they suggested a role of the STG in a phonological working memory network.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies investigating the effect of external distortions on speech processing generally do so use added background noise (Davis & Johnsrude, 2003;Scott, Rosen, Wickham, & Wise, 2004;Wong et al, 2008). Wong et al presented words in background noise (multi-talker babble) in various signal-to-noise (SNRs) in decibel (dB) ratios (quiet, +20 dB, −5 dB) and reported an increase in the Blood-Oxygenated Level Dependent (BOLD) response for decreasing SNRs across a wide network of cortical regions, involving Superior Temporal Gyrus (STG) including Heschl's Gyrus (HG) bilaterally, left Inferior Frontal Gyrus (IFG) and the Frontal Operculum (FO).…”
Section: Introductionmentioning
confidence: 99%
“…Some distortions are related to properties of the channel between conversation partners (external distortions), such as background noise, interruptions or signal degradation due to speaking over a telephone (Davis & Johnsrude, 2003;Wong, Uppanda, Parrish, & Dhar, 2008). Other distortions are related to the way in which the speaker produces utterances (speakerrelated distortions), e.g., those due to anatomical and physiological differences between speakers, differences in speech rate, accent differences related to speakers' regional background, and differences related to speech style such as mumbling, reading aloud versus spontaneous speech (Adank, Evans, Stuart-Smith, & Scott, 2009;Dupoux & Green, 1997;Floccia, Goslin, Girard, & Konopczynski, 2006;Peterson & Barney, 1952).…”
Section: Introductionmentioning
confidence: 99%
“…It has been associated with numerous functions such as auditives processing (Humphries et al 2001), learning and memory (Schiltz et al 1973), social cognition (Ingrid et al 2007), and language processing (Hermann & Wyler 1988). STG (BA 22) plays the role in auditives language reception and processing (Wong et al 2008). From Table 1, L-STG and L-TP show extended and higher activation as compared to R-STG and R-TP both during AIQ and AIN.…”
Section: Discussionmentioning
confidence: 96%
“…Scott et al (2004) suggested that there is an engagement of perception and cognitive networks during listening to speech in noisy condition. In terms of the brain functional anatomy, the superior temporal gyrus (STG) plays a central role in the perception of speech (Wong et al 2008) and non-speech stimuli (Hall et al 2002).…”
Section: Introductionmentioning
confidence: 99%